EVALUATION OF SOME MINERAL IN SHEEP IN BASRA - Israa abdul wadood; Bahjah ghassan (Basrah Journal of Veterinary Research)
The present study was conducted in Basra province to evaluate of some minerals (copper,, zinc and cobalt) in sheep. The study constituent examination of 1400 sheep and 200 of it showed sings of mineral deficiency and 25 as a control, the study include: clinical, hematological examination, and level of serum(copper, zinc, and cobalt). A number of 200 (14.2%) sheep revealed a clinical signs of mineral deficiency from total of (1400) sheep which were clinically examined in this study, And the study showed that the values of copper, zinc, and cobalt in serum were significantly low (0.15±0.03ppm, 0.73±0.35ppm, 0.57±0.12ppm). and the most important clinical signs presented by alopecia (47.5 %), parakiratosis (18%), diarrhea (11.5%), pale mucous membrane (49%), lacrimation (6%), ataxia (4%). Also the study reveal that the body temperature within normal (39.47±0.33 C°), but increase of pulse rate, and respiratory rate in affected animals were (90.48± 4.53Min, 33.99±0.29 Min) respectively. And the study showed that the RBCc of affected sheep significantly low (6.57±0.10 *106/ml), also the PCV, Hb, MCV, MCH, were significantly low (19.75±0.24 %, 6.88±0.11 g/L, 31.07±0.49 fl, 11.06±0.53 pg) respectively, whereas MCHC in affected sheep was significantly high (34.92±0.45 %) and the mean of WBCc of affected sheep were(6.43±0.11103/ml) and there is no significant different when compared with control.